1H and 13C NMR Assignments of Cytotoxic 3S-1,2,3,4-Tetrahydro-β-carboline-3-carboxylic Acid from the Leaves of Cichorium endivia - Fu-Xin Wang; An-Jun Deng; Jin-Feng Wei; Hai-Lin Qin; Ai-Ping Wang (Journal of Analytical Methods in Chemistry)
An amino acid, 3S-1,2,3,4-tetrahydro-β-carboline-3-carboxylic acid, was isolated for the first time from the leaves of Cichorium endivia. The complete assignment of its 1H and 13C NMR spectroscopic data was carried out also for the first time based on extensive 1D and 2D NMR experiments. Cytotoxicity of this isolated compound against HCT-8 and HepG2 human cancer cell lines was evaluated for the first time, with moderate activities being found.